2020
DOI: 10.1186/s12883-020-01965-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection, seasonality and younger age predicting incident Bell’s palsy among black South Africans

Abstract: Background Although South Africa (SA) is facing a high prevalence of HIV infection, there is no literature from this region on a link between Bell’s palsy and HIV. The aim of this study was to identify the occurrence of Bell’s palsy in relation to demographics, seasons and HIV status among black South Africans. Methods This retrospective cohort was conducted among adult black patients, without Bell’s palsy in 2003, presenting to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There have been several studies on the seasonality of Bell palsy and SSNHL. Studies have revealed that Bell palsy was significantly higher during the cold season, [ 17 , 21 , 22 ] although other studies have shown unclear association between Bell palsy and seasons. [ 16 , 23 ] One study revealed that the incidence of SSNHL peaked in autumn, [ 18 ] but most other studies showed nonsignificant distributions for seasons.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies on the seasonality of Bell palsy and SSNHL. Studies have revealed that Bell palsy was significantly higher during the cold season, [ 17 , 21 , 22 ] although other studies have shown unclear association between Bell palsy and seasons. [ 16 , 23 ] One study revealed that the incidence of SSNHL peaked in autumn, [ 18 ] but most other studies showed nonsignificant distributions for seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, the fluVc is only administered for a short period each year, especially from October to December, middle autumn to early winter . It may take bias when using SCCS if the incidence of BP varies with different seasons, which is a concern because previous studies have examined the association between seasonal variation and the onset of BP . Fortunately, the present findings indicated that seasonality did not affect BP incidence in this SCCS.…”
Section: Discussionmentioning
confidence: 61%
“…6,7,9 It may take bias when using SCCS if the incidence of BP varies with different seasons, which is a concern because previous studies have examined the association between seasonal variation and the onset of BP. 22,[44][45][46][47] Fortunately, the present findings indicated that seasonality did not affect BP incidence in this SCCS. The diagnosis of BP is made after various conditions that mimic BP have been excluded.…”
Section: Discussionmentioning
confidence: 73%
“…In a study with 591 patients in Germany, the numbers of patients with Bell's palsy were significantly different according to month, with the highest noted in December and the lowest in July [11]. In a study of 311 black patients with Bell's palsy in South Africa, winter was a significant predictor of Bell's palsy [14].…”
Section: Discussionmentioning
confidence: 94%